Multi-Channel Queue System for Outpatient Registration Services at Mitra Sejati Medan General Hospital in 2023 - Maulana, Fajar; Nasution, Dwiana Arianty (SEAN Institute, 2023)
Queue is a condition where a group of people, components or machines that need service must wait in a certain order before finally getting service. Data analysis of this study using quantitative analysis techniques This analysis was used to determine the efficiency of queues at Mitra Sejati Medan General Hospital. Conclusion Based on the analysis of the application of the current queuing system at Mitra Sejati Medan General Hospital, it can be drawn as follows: Registration service of Mitra Sejati Medan General Hospital, the type of queuing system applied is the type of queue model Multi Channel Single Phase or M/M/s. The service discipline applied at Mitra Sejati Medan General Hospital is the First In First Out (FIFO) service discipline. To maintain the performance of the queuing system applied to outpatient registration services at Mitra Sejati Medan General Hospital, it is necessary to consider the level of customer arrival and the level of queues that occur every day, especially during the time period of 10.00 - 11.00 at the outpatient registration counter because crowds of visitors occur at that hour.